2000
DOI: 10.1164/ajrccm.162.4.9911033
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered Respiration in Phenotypically Normotensive, Genetically Hypertensive Rats

Abstract: Increased prevalence of sleep-related breathing disorders has been reported in patients with essential hypertension and we have described disordered breathing in spontaneously hypertensive rats, an animal model of genetic hypertension. The mechanisms coupling hypertension to respiratory dysfunction during sleep remain, however, largely unknown. To determine if sleep-related respiratory disorder reflects cardiovascular derangement or, alternatively, represents an independent phenotype in hypertensive rats, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Reductions in spontaneous sleep apnea (>2 respiratory cycles) occurred using either pharmacologic agent. The latter study concluded that a persistent sleep-related breathing disorder occurred despite effective cardiovascular normalization by neonatal hydralazine in the phenotypically normotensive but genetically hypertensive rat (Carley et al, 2000). In the former study mirtazapine was observed to suppress apnea >2 respiratory cycles in all sleep stages in adult rats and attributed this effect to a mixed agonist/antagonist profile at serotonin receptors (Carley and Radulovacki, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Reductions in spontaneous sleep apnea (>2 respiratory cycles) occurred using either pharmacologic agent. The latter study concluded that a persistent sleep-related breathing disorder occurred despite effective cardiovascular normalization by neonatal hydralazine in the phenotypically normotensive but genetically hypertensive rat (Carley et al, 2000). In the former study mirtazapine was observed to suppress apnea >2 respiratory cycles in all sleep stages in adult rats and attributed this effect to a mixed agonist/antagonist profile at serotonin receptors (Carley and Radulovacki, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Thus NO production in peripheral chemoreceptors or the central nervous system alone did not solely contribute to the results reported in this study; rather, a remodeling of central regulation of frequency may have occurred. Cap treatment, however, did not prevent the development of periodic breathing, a finding also described in SHR (4). Additional mechanisms by which Cap may maintain ventilation is altering reflex responses to elevated blood pressure (10).…”
Section: Discussionmentioning
confidence: 78%
“…The natural models of sleep apnea include the English bulldog, the historic natural model of spontaneous obstruction (Hendricks et al, 1987), the sleep-related central apnea models [e.g., Sprague-Dawley rats (Carley et al, 2000), spontaneously hypertensive (SH) rats (Carley et al, 1998), C57BL/6J (Julien et al, 2003; Liu et al, 2010)], and the Zucker obese rat in which apnea is obesity-related (Ray et al, 2007; Lee et al, 2008; Iwasaki et al, 2012). The experimentally-induced models (e.g., the sleep deprivation model, induced airway obstruction and the CIH model) are the most widely used.…”
Section: What Models Are Available To Study Ht Related To Osa?mentioning
confidence: 99%